Evidências de validade e estudos preliminares de normatização do teste infantil informatizado para avaliação das funções executivas - TAFE - Elage, Glauce Karine Conti de Freitas (2021)
Executive functions include high-level cognitive skills such as working memory, inhibitory control and cognitive flexibility. These are skills that enable the management and regulation of thoughts, emotions and behaviors, thus being relevant skills for social, cognitive and emotional development. Considering the importance of these functions, it is relevant to have instruments for their assessment, which must be done using instruments with psychometric quality. This study aimed to investigate the psychometric properties and provide preliminary normative data from a computerized instrument that assesses the three basic skills of executive functions of children aged 4 to 10 years, called the Executive Function Assessment Test (TAFE). The newly created instrument has all its computerized functioning, which allows for a greater standardization of instructions, hinders application and / or registration errors, in addition to having a playful presentation, which may be more suitable for children. Although the instrument presents psychometric studies previously performed, there is a need for further analysis, in order to provide an instrument with more reliable psychometric data. 232 children aged 4 to 10 years participated in this study, divided into two groups: (1) 213 children from private schools in the cities of Goiânia and São Paulo, without complaints of school difficulties; (2) 21 children from private schools in Goiânia, with a recent diagnosis of Attention Deficit / Hyperactivity Disorder. As instruments for both groups, TAFE was used, and for children in group 2, in addition to TAFE, the Wechsler Intelligence Scale for Children (WISC-IV). The factor analyzes confirmed that the structure of the collected data fit the structure proposed in the literature on executive functions; analyzes of variance of age and school level and between groups (control and clinical) indicated validity of the instrument and, also, significant correlations were found in relation to other measures of executive functions and minor and nonsignificant correlations with tasks that did not higher demand for executive functions. Tables with normative data were derived by age (4 to 10 years) and by level of education (pre-school to the 5th year of elementary school). Thus, the study revealed relevant psychometric findings that indicated the adequacy of TAFE, which allows the use of an unprecedented computerized instrument, with psychometric data, preliminary standardization tables, by health and education professionals, being therefore a relevant study for the performance of professionals. The study presented, as limiting factors, the number of participants, the absence of a sample from other clinical groups and a sample from public schools, which were restricted due to the difficulties caused by the COVID-19 pandemic.